Salud sexual y reproductiva en círculos de espiritualidad femenina (Argentina, 2014-2021) - Felitti, Karina (Revista cultura y religión, 2022)
This article analyzes the definitions and practices oriented to sexual and reproductive healthcare of women and the healing of situations experienced around bodily processes such as menstruation, pregnancy, childbirth and abortion. All these definitions and practices are proposed in women's circles and networks for the dissemination of feminine spirituality. It is based on qualitative research carried out in the City of Buenos Aires and Santa Fe, between 2014 and 2021. Various techniques for data collection, such as participant observation in women's circles and interviews to their facilitators and participants are applied in this research. In addition, we analyzed the contents shared by the facilitators in their social networks, and books that are part of their training. Findings are discussed and understood under the light of an arena of popularization of definitions and practices of feminine spirituality, social and political recognitions of feminisms, and public policies on sexual and reproductive health in contemporary Argentina.